2019
DOI: 10.1002/micr.30517
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of the perforators and the accessory saphenous vein in a profunda femoris artery perforator flap for additional venous anastomosis: A cadaveric study and clinical application

Abstract: Background The profunda femoris artery perforator (PAP) flap is gaining popularity in microsurgical reconstruction. To establish a safer flap elevation technique, we focused on the topology of the accessory saphenous vein in the medial thigh area. We hypothesize that including the accessory saphenous vein in a PAP flap results in safer PAP flap transfer with two venous drainage systems. The aim of this study was to describe the anatomical relationship between the perforators and the accessory saphenous vein in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
(37 reference statements)
1
9
0
Order By: Relevance
“…10 Satake et al and Karakawa et al also demonstrated similar results of the distance of the perforators from the groin crease and size of perforators. 9,17 Our findings demonstrate the mean dominant profunda perforator location is 7.04 cm distal to the IGF. With traditional tPAP flap design, this would result in an eccentrically located perforator since the inferior border of the tPAP flap is generally 6 to 8 cm inferior to the gluteal fold.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…10 Satake et al and Karakawa et al also demonstrated similar results of the distance of the perforators from the groin crease and size of perforators. 9,17 Our findings demonstrate the mean dominant profunda perforator location is 7.04 cm distal to the IGF. With traditional tPAP flap design, this would result in an eccentrically located perforator since the inferior border of the tPAP flap is generally 6 to 8 cm inferior to the gluteal fold.…”
Section: Discussionmentioning
confidence: 62%
“…10 Satake et al and Karakawa et al also demonstrated similar results of the distance of the perforators from the groin crease and size of perforators. 9 17…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the greatest advantages of the PAP flap is that a relatively large volume of flexible skin paddle and fat tissue with a long pedicle can be harvested from an inconspicuous donor site in every surgical position. [23][24][25] Therefore, PAP flap can be harvested from the thigh, which is slightly farther from the back, simultaneously with tumor resection. Especially in the prone position, PAP flap can be one of the optimal donor sites for reconstruction of the posterior trunk because of the limited number of flaps which can be elevated simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is the lack of description of the venous anatomy. However, the vascular anatomy of the gracilis muscle flap is well described in the literature (Azizzadeh & Pettijohn, 2020) and also, the accessory saphenous vein can be included in the PAP flap to decrease the chances of congestion of the skin island (Karakawa et al, 2020).…”
Section: Discussionmentioning
confidence: 99%